Complement System as a New Target for Hematopoietic Stem Cell Transplantation-Related Thrombotic Microangiopathy - Gianluigi Ardissino; Valentina Capone; Silvana Tedeschi; Luigi Porcaro; Massimo Cugno (Pharmaceuticals, 2022)
Thrombotic microangiopathy (TMA) is a complication that may occur after autologous or allogeneic hematopoietic stem cell transplantation (HSCT) and is conventionally called transplant-associated thrombotic microangiopathy (TA-TMA). Despite the many efforts made to understand the mechanisms of TA-TMA, its pathogenesis is largely unknown, its diagnosis is challenging and the case-fatality rate remains high. The hallmarks of TA-TMA, as for any TMA, are platelet consumption, hemolysis, and organ dysfunction, particularly the kidney, leading also to hypertension. However, coexisting complications, such as infections and/or immune-mediated injury and/or drug toxicity, together with the heterogeneity of diagnostic criteria, render the diagnosis difficult. During the last 10 years, evidence has been provided on the involvement of the complement system in the pathophysiology of TA-TMA, supported by functional, genetic, and therapeutic data. Complement dysregulation is believed to collaborate with other proinflammatory and procoagulant factors to cause endothelial injury and consequent microvascular thrombosis and tissue damage. However, data on complement activation in TA-TMA are not sufficient to support a systematic use of complement inhibition therapy in all patients. Thus, it seems reasonable to propose complement inhibition therapy only to those patients exhibiting a clear complement activation according to the available biomarkers. Several agents are now available to inhibit complement activity: two drugs have been successfully used in TA-TMA, particularly in pediatric cases (eculizumab and narsoplimab) and others are at different stages of development (ravulizumab, coversin, pegcetacoplan, crovalimab, avacopan, iptacopan, danicopan, BCX9930, and AMY-101).